Cardiovascular imaging Noninvasive assessment of cerebral artery stenoses from anatomic computed tomography angiography - Qi, Xiaolong; Zhou, Fangyu; Wan, Jun; Zhou, Lin; Xu, Wei; Cheng, Juan; Mao, Yu; Ma, Wanrong; Ji, Wenbin; Yang, Changqing (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Trans-stenotic pressure gradient (TSPG) and fractional flow reserve (FFR) are well-validated hemodynamic indices to assess the ischemic severity of arterial stenoses. However, they have significant restrictions in practice due to invasiveness and high cost. Recently, a noninvasive assessment of FFR from computed tomography (CT) angiography has been well validated in evaluating functional coronary stenoses. We present a case of a 65-year-old woman with cerebral artery stenoses demonstrated by clinical symptoms, transcranial Doppler ultrasound and CT angiography, aiming to transplant the noninvasive functional diagnosis, for the first time, to cerebral artery stenoses and test a computational workflow of noninvasive TSPG and FFR.